2009
DOI: 10.1002/j.2050-0416.2009.tb00341.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Ochratoxin A Levels in White Wine by Yeast Treatments

Abstract: This paper describes the abilities of 21 yeast strains isolated from six different wine‐grapes of Turkey to bind ochratoxin A (OTA). Viable (108 CFU/mL) and heat‐treated yeast cells were incubated both in phosphate‐buffered saline (PBS) and white wine containing 10 ng OTA per mL for 4 h at 25°C. After centrifugation, the concentration of OTA was measured in the supernatant fraction using a high‐performance liquid chromatography system coupled with fluorescence detector. The adsorption abilities of OTA by viabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 14 publications
0
25
0
5
Order By: Relevance
“…Some authors reported decreasing ochratoxin levels during winemaking [26,27,[30][31][32]. In previous work, we suggested that physical binding to the yeasts biomass might be responsible for ochratoxin A decrease [33].…”
Section: Introductionmentioning
confidence: 69%
“…Some authors reported decreasing ochratoxin levels during winemaking [26,27,[30][31][32]. In previous work, we suggested that physical binding to the yeasts biomass might be responsible for ochratoxin A decrease [33].…”
Section: Introductionmentioning
confidence: 69%
“…Different authors have described that yeast can potentially be used for removing OTA from wine [29]. Several hypotheses could be made: yeast could use OTA as a source of carbon for obtaining energy, thereby reducing the OTA levels in these types of wines [17].…”
Section: Resultsmentioning
confidence: 99%
“…The increasing trend towards OTA occurrence in grape, grape juice and wine has led to a focus on toxin removal mediated by yeasts . However, to the best of our knowledge, there are no comprehensive studies on the influence of physicochemical factors such pH, temperature, ethanol content and incubation time on OTA removal by S. cerevisiae .…”
Section: Discussionmentioning
confidence: 99%
“…reported that some strains of the species S. cerevisiae and Kloeckera apiculata decreased the amount of OTA in a synthetic must by 0.25–0.5‐fold, whereas other strains did not show any effect. This may be due to the different cell wall structures of yeasts . In particular, the cell wall of S. cerevisiae is made of mannoproteins bound to oligopolysaccharides, which remain exposed on the outside of the cell.…”
Section: Discussionmentioning
confidence: 99%